2023
DOI: 10.1039/d2fo02959f
|View full text |Cite
|
Sign up to set email alerts
|

Galactooligosaccharides ameliorate dietary advanced glycation end product-induced intestinal barrier damage in C57BL/6 mice by modulation of the intestinal microbiome

Abstract: Advanced glycation end products (AGEs) are increasingly recognized as a potentially pathogenic component of processed foods, and long-term consumption of dietary AGEs triggers disruption of intestinal barrier integrity and increases...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In particular, Sprague-Dawley rats exposed to a high AGE diet for 6, 12, or 18 weeks showed reduced α-diversity, altered crypts, goblet cell depletion, dysregulated expression of the colonic tight junctions zonulin-1 and occludin-1, and increased intestinal permeability, especially in the group fed a high AGE diet for 18 weeks [42]. In line with these findings, Nie et al reported that an AGE-enriched diet affected intestinal barrier integrity and microbial composition in C57BL/6 mice, while treatment with prebiotic galactooligosaccharides (GOS) limited these alterations by decreasing the frequency of Akkermansia muciniphila and increasing the number of goblet cells, tight junction expression, and short-chain fatty acid levels [43]. Furthermore, mice transplanted with fecal content from the AGE-treated group developed an altered mucus barrier, while those receiving feces from animals treated with GOS were protected [43].…”
Section: Agesmentioning
confidence: 77%
See 1 more Smart Citation
“…In particular, Sprague-Dawley rats exposed to a high AGE diet for 6, 12, or 18 weeks showed reduced α-diversity, altered crypts, goblet cell depletion, dysregulated expression of the colonic tight junctions zonulin-1 and occludin-1, and increased intestinal permeability, especially in the group fed a high AGE diet for 18 weeks [42]. In line with these findings, Nie et al reported that an AGE-enriched diet affected intestinal barrier integrity and microbial composition in C57BL/6 mice, while treatment with prebiotic galactooligosaccharides (GOS) limited these alterations by decreasing the frequency of Akkermansia muciniphila and increasing the number of goblet cells, tight junction expression, and short-chain fatty acid levels [43]. Furthermore, mice transplanted with fecal content from the AGE-treated group developed an altered mucus barrier, while those receiving feces from animals treated with GOS were protected [43].…”
Section: Agesmentioning
confidence: 77%
“…In line with these findings, Nie et al reported that an AGE-enriched diet affected intestinal barrier integrity and microbial composition in C57BL/6 mice, while treatment with prebiotic galactooligosaccharides (GOS) limited these alterations by decreasing the frequency of Akkermansia muciniphila and increasing the number of goblet cells, tight junction expression, and short-chain fatty acid levels [43]. Furthermore, mice transplanted with fecal content from the AGE-treated group developed an altered mucus barrier, while those receiving feces from animals treated with GOS were protected [43].…”
Section: Agesmentioning
confidence: 83%
“…In a dose-responsive pattern, milk GOS have been found to modulate TEER, intensifying mucin gene expression and mucin abundance . Such GOS also elevate the expression of OCC, claudin-1, MUC2, TFF3 , RETNLB , and CHST5, thus enhancing the mucosal barrier function by directly stimulating intestinal goblet cells. , Moreover, goat milk-derived GOS have been observed to play a vital role in fortifying and restoring intestinal integrity after damage from DSS-induced colitis . A study identified that feeding neonatal NEC mice with yak milk GOS can effectively regulate the TLR-4/NF-kB inflammatory pathway and inhibit the expression of inflammatory factors (IL-6, IL-1, and TNF-α) to alleviate the occurrence of NEC .…”
Section: The Guardian Effect Of Milk Ingredients On the Gut Barriermentioning
confidence: 99%